CO₂ emission reduction through fuel switching from liquid to gaseous fuels in an Indonesian oil refinery toward a sustainable energy transition case study in Sumatra refinery - Wulandari, Niken; Saksono, Nelson (Edelweiss Applied Science and Technology, 2025)
Fossil fuels are expected to remain the primary contributors to Indonesia’s greenhouse gas (GHG) emissions by 2030, accounting for an estimated 57% of the total national emissions. A significant portion of these emissions originates from oil refinery operations, particularly due to the persistent use of high-carbon residual liquid fuels. In light of Indonesia’s commitment to achieving net-zero emissions by 2060, this study investigates the effectiveness of partial fuel substitution as a mitigation strategy. Using the American Petroleum Institute [1] activity-based emissions estimation methodology with specific emission factors, the study quantifies CO₂ emissions from a selected refinery unit in Sumatra, Indonesia. A simulation scenario involving the replacement of up to 56% of liquid fuels with gaseous fuels was conducted. The results indicate a potential CO₂ emission reduction of approximately 38%, demonstrating the significant environmental benefits of this transition. The findings highlight the technical feasibility of fuel switching within refinery operations and its alignment with Indonesia’s Nationally Determined Contribution (NDC) targets. These insights may inform future policy development and support strategic initiatives toward a low-carbon transition in the energy and industrial sectors.